Uterine Balloon Tamponade for the Treatment of Postpartum Hemorrhage: A Systematic Review and Meta-analysis. Issue 1 (24th March 2021) - Suarez, S.; Conde-Agudelo, A.; Borovac-Pinheiro, A.; Suarez-Rebling, D.; Eckardt, M.; Theron, G.; Burke, T.F.
Abstract : ( Am J Obstet Gynecol . 2020;222:293.e1–293.e52) A leading cause of worldwide maternal death is postpartum hemorrhage (PPH). In 2017, there were 38, 000 maternal deaths worldwide, with over 90% occurring in low- and middle-income countries. In addition, an annual 1.5 million women experience hemorrhage-related complications during pregnancy or postpartum. Effective treatment for PPH includes uterotonics, uterine massage, uterine artery embolization, tranexamic acid, uterine balloon tamponade (UBT), and additional surgical intervention. The aim of this study was to conduct a meta-analysis and systematic review to determine the effectiveness, efficacy, and safety of UBT for the treatment of PPH.